Formulasi Orally Disintegration Tablet (ODT) Candesartan Cilexetil Dengan Croscarmellose Sodium dan Crospovidone Sebagai Superdisintegrant - Nurista Dida Ayuningtyas; Yahya Febrianto; Tutut Lutfi (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2021)
Candesartan cilexetil is a group of selective AT1 hypertension drugs (angiotensin II receptor antagonist 1). The drawback of candesartan cilexetil in conventional tablets is that it cannot be used for geriatric patients who have difficulty swallowing tablets, patients with developmental disorders of the muscle and nervous system (tremors), and in schizophrenic patients that lead to poor patient compliance, so to overcome this problem alternative dosage forms are made new namely ODT candesartan cilexetil. This study aims to determine the effect of the combination of superdesintegrant croscarmellose sodium and crospovidone on the quality test of the physical properties of tablets. Candesartan cilexetil ODT tablets bolted by direct compression method with variations in levels of superdesintegrant croscarmellose sodium and crospovidone 2: 3,5%, 2,75: 2,75%, 5: 0,5%, 4,25: 1,25 %, 3,5: 2%. Tests conducted to determine the physical quality of candesartan cilexetil ODT, namely organoleptic, weight uniformity, size uniformity, hardness, brittleness, disintegration time, wetting time and water absorption ratio. Showed an increase in the use of crospovidone (5%) and a decrease in croscarmellose sodium (0.5%) had a greater effect on the disintegration time because it could make the tablet porous when in contact with water so that it would accelerate the disintegration time of 29.167 seconds and increase the speed of wetting the tablets 25.33 seconds. The combination of superdisintegrant croscarmellose sodium and crospovidone (0.5: 5%) in formula 3 can provide physical properties that meet the best quality ODT requirements for candesartan cilexetil.